Discourse Of Informed Consent In The Application Of Cardiac Surgery Techniques In Indonesia - Riyantika, Annisa (Jurnal Hukum Malahayati, 2024)
Informed Consent is an important thing in medical services, recently there have been cases of  problems that start from the incompatibility of Informed Consent with factual actions carried  out by the hospital. This has been explained in Jo Law No. 44 of 2009 concerning hospitals  Article 37 paragraph 1 which states that every medical action taken in the hospital must obtain  the consent of the patient and his family. The purpose of this article is to analyze the Informed  Consent Relationship between Doctors and Patients Legally in the Application of Cardiac  Surgery Techniques in Indonesia and to analyze the Application of Informed Consent in the  Application of Cardiac Surgery Techniques. The method used in this research is the normative  juridical method. The normative juridical approach is carried out by conducting a study of the  principles, regulations and legislation in force with regard to the legal issues to be discussed.  The results of this study are the existence of an informed consent relationship between doctors  and patients and the application of informed consent in heart surgery in Indonesia.